In vivo evaluation biological of protein quality of hamburgers containing fibers - Tiffany Prokopp Hautrive; Ângela Souza Rodrigues; Karine Ines Bolson Moro; Gilberti Helena Hübscher; Ernesto Hashime Kubota (O Mundo da Saúde, 2015)
This study aimed to evaluate the protein quality of hamburgers made with chitosan and golden flaxseed meal defatted through biological response in rats. Male Wistar rats were fed for 28 days with the following experimental treatments: protein diet and diets diet with casein-tests where casein was replaced by traditional burger meal (HT), burger meal with chitosan (HQ) and burger meal with golden defatted flaxseed meal (HLD). Weight gain was evaluated, food consumption, the amount of protein intake, the protein quality ratio (PER), Net protein ratio (NPR) and true digestibility (DV) of the animals fed with different types of flour burger . Weight gain was higher in the HT group. The PER ranged from 2.33 (casein) to 1,94 (HQ) and the NPR 2,65 (casein) to 2,22 (HQ). The DV for hamburger meal was lower than 90%. It was found that the burgers with fibers offered to animals in the form of flour showed lower efficiency compared to casein. However they have a good protein quality, a fact that allows their inclusion in diets of healthy individuals.